PENGARUH CORPORATE GOVERNANCE DAN KONSERVATISME AKUNTANSI TERHADAP TAX AVOIDANCE (Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia periode 2014-2016 ) - Yulistian, Andika; Nasir, Azwir; Hasan, Mudrika Alamsyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to examine the effect of Corporate Governance and Accounting Conservatism on Tax Avoidance of the mining companies listed on Indonesia Stock Exchange in 2014-2016. Corporate Governance was elaborated into audit quality, audit committee, and institutional ownership. The Population of this study is all of mining companies which is listed in Indonesia Stock Exchange. The sample of this study is 45 from 15 companies that meet the sampling criterias and listed in Indonesia Stock Exchange. The analytical technique that is used to perform the hypothesis testing is purposive sampling. Data are analyzed using multiple regression method using SPSS (Statictical Product and Service Solution) version 25. The results showed that audit quality affect the tax avoidance, it comes from the significance that is 0,001. Institutional ownership affect the tax avoidance, it comes from the significance that is 0,022. Accounting conservatism affect the tax avoidance, it comes from the significance that is 0,001 while the audit committee did not affect the tax avoidance, it comes from the significance that is 0,169.Keywords : audit quality, institutional ownership, accounting conservatism, audit committee, tax avoidance